Strategi Digital Marketing X Wedding Organizer - Wina Rusdarina; Tresna Wiwitan (Jurnal Riset Public Relations, 2021)
Abstract. The business development in the service sector is currently growing rapidly, especially in the wedding organizer industry. One of them is the Rostic Wedding Organizer. The large number of wedding organizers that have sprung up has created intense competition. To face the tough competition, Rostic Wedding Organizer conducted a marketing public relations strategy to achieve the company's goals. The objectives of the issues raised were (1) To find out the reasons why Rostic chose the high-end market as the main target target (2) To find out and analyze Rostic's publication method so that it was easily recognized in a short time (3) To find out and analyze the Rostic branding method for get the right target. To reveal this problem, this study uses a type of qualitative research that is useful for providing facts and data about the Rostic Wedding Organizer marketing public relations strategy. Then the data is analyzed using a case study approach that provides development on the research field under study. Then the data collection techniques used observation techniques, in-depth interviews with key informants, and documentation. While the theory used in this research is the excellent two-way symmetric model theory. The Result of the research of Rostic Wedding Organizer marketing piblic relations strategy were determining the target market, Rostic choosing the high-end market as the main target, then Rosric published using digital marketing and influencer marketing, after that Rostic did branding through product branding to reach the target market. Abstrak. Perkembangan bisnis di bidang jasa saat ini semakin berkembang pesat, terutama pada industri wedding organizer. Salah satunya adalah Rostic Wedding Organizer. Banyaknya wedding organizer yang bermunculan membuat adanya persaingan yang ketat. Untuk menghadapi persaingan yang ketat Rostic Wedding Organizer melakukan strategi marketing public relations untuk mencapai tujuan perusahaan. Tujuan dari masalah yang diangkat yaitu untuk mengetahui (1) alasan mengapa Rostic memilih market kelas atas sebagai taregt sasaran utama (2) menganalisis cara publikasi Rostic agar mudah dikenal dalam waktu yang singkat (3) menganalisis cara branding Rostic untuk mendapatkan target yang tepat sasaran. mengungkapkan persoalan tersebut penelitian ini menggunakan jenis penelitian kualitatif yang berguna memberikan fakta dan data mengenai strategi marketing public relations Rostic Wedding Organizer kemudian data tersebut dianalisis menggunakan pendekatan studi kasus yang memberikan pengembangan terhadap bidang kajian yang diteliti. Kemudian teknik pengumpulan data menggunakan teknik observasi, wawancara secara mendalam kepada key informan, dan dokumentasi. Sedangkan teori yang digunakan dalam penelitian ini adalah teori excellent two-ways symmetric model. Hasil penelitian Strategi Marketing Public Relations Rostic Wedding Organizer yaitu: menentukan target pasar, Rostic memilih market kelas atas sebagai target utama, kemudian Rostic melakukan publikasi menggunakan digital marketing dan influencer marketing, setelah itu Rostic melakukan branding melalui product branding untuk mencapai target pasar yang dituju.